Editorial (African Journal of Science, Technology and Social Sciences, 2022)
Welcome to the inaugural issue of the African Journal of Science Technology and Social Sciences: a peer-reviewed, multidisciplinary journal in the field of Science, Technology and Social sciences.  Launched by Meru University of Science and Technology, AJSTSS provides a cross-disciplinary and international forum for researchers to disseminate innovative research and practices that preserve the integrity, life-cycle performance, and resilience of new or existing knowledge.The many challenges towards achieving improved publications must be addressed with proactive, holistic, and multidisciplinary approaches. This journal is facilitating an in-depth dialogue and synergistic collaboration between both the academia and industry.  We aspire to establish AJSTSS as the flagship journal in the various emerging fields with a focus on creating consistent contributions.All abstracts and manuscripts have gone through a rigorous yet relatively rapid peer-review process, which translates to benefits such as timeliness of publication, widespread dissemination, high visibility, and likelihood of high citations and broader impacts. We are presenting cutting-edge innovations and the latest insights and strive to maintain quality.AJSTSS provides the most complete and reliable source of information on current developments in the field and facilitate peer-to-peer exchange and dialogue beyond the conventional discipline boundaries, leading towards proactive and systematic solutions that enhance reliability. The emphasis is on publishing high-quality articles, including original research papers, research notes, and reviews - all of which contribute to advancing the knowledge base of infrastructure preservation and resilience and bridging the gaps between different disciplines and stakeholders relevant to the development and implementation of best solutions.In this first issue we have published abstracts from the Inaugural Meru University of Science and Technology International Conference Proceedings (MUSTIC 2022).Welcome!From the Editor in ChiefProf. Eric Muchiri (Ph.D.)